ANALISIS ATAS ANNUAL REPORT YANG SUDAH TERINTEGRATED PT. BFI FINANCE INDONESIA TBK: STUDI INTERPRETIVE DALAM PRESPEKTIF SEMIOTIKA DAN RETORIKA - B2091171003, DIMAS PATRIA AKBAR WIBOWO (MAKSI UNTAN, 2019)
The research aimed at understanding aspects of semiotics and rhetoric in integrated reporting PT BFI Finance Indonesia Tbk between 2016 and 2017. The Research used qualitative methodology employing content analysis approach. The sample of the research was state owned enterpriseÂ  wich runs in finance and has more that 10 trillion assets.Â  The research showed that semiotics aspects was confirmed in annual report of the company. Integrated annual report of PT BFI Finance Indonesia Tbk was made to create rhetorical story to build positive image and to get legal legitimate from stakeholders. The research has two limited result in a way that the object of the study only focused on one company, that is PT BFI Finance Indonesia Tbk, as a result the research finding was not same. If it is implemented in other company in the future, the result might be diffrent. Second, since the integrated reporting on annual report of PT BFI Finance Indonesia Tbk used semiotics interpretive paradigm, subjectivity might happen. Â Keywords: Integrating Reporting,Â  Rhetoric, Semiotics.DAFTAR PUSTAKAArgonda, Antonio. (2011). â€œStakeholder Theory and Value Creationâ€.Â Â Â Â Â Â Â Â  Working Paper, WP-992.Â Arnold, Carroll. C. (1982). â€œIntroduction in The Realm of Rhetoric Ch. Perelman Ed (Eds) Kulbackâ€. Notre Dame: The University of Notre Dame Press, pp.vii-xx.Â Brennan, Niamh dan Sidney J. Gray. (2000). â€œRhetorik and Argument ini Financial Reporting : disclosures in profit forecasts and takeover documentsâ€. ACCA Occasional Research Paper No 31, Certfied Accountants Educational Trust, London, ISBN 1-85908-317-X.Bogdan, Robert C. dan Biklen Kopp, (1982), Qualitative Research for Education: An Introduction to Theory and Methods. Allyn and Bacon, Inc.: Boston London.Â Budiani, Rizka Julia. (2011). â€œNarsisme dalam Pelaporan Keuangan: Analisis Semiotik atas laporan keuangan Perusahaan yang mengalami Kerugianâ€. Skripsi, Semarang: Fakultas Ekonomi Universitas Diponegoro.Camiciottoli, Belinda Crawford. (2012). â€œOral Finance Reporting: A Rhetorical Analysis of Earnings Callâ€. Skripsi, Franco Angeli, Milano, Italy: Universitasdi PisaCarter P. Dan N. Jackson. (2004) â€œFor the sake of Argument: Towardsan Understanding of Rhetoric as Processâ€. Jurnal Manajemen, 41:3, pp.469-491Chariri, Anis. (2007). â€œRhetorics in Financial Reporting: An Interpretive case Studyâ€,Â  jurnal Akuntansi dan Keuangan, Vol 12, No 2, pp.53-70Chariri, A. dan Nugroho. F. A. (2009). â€œRetorika dalam Pelaporan Corporate Social Responsibility : Analisis Semiotik atas Sustainibility Reporting PT. Aneka Tambang, Tbk. SimposiumÂ C.S Peirce, (1919).Â  â€œTeori segitiga makna atau triangel meaningâ€, jurnal Akuntansi dan Keuangan, Vol 15, No 34, pp 67-70Diajeng, et al. (2014). â€œNarsisme dalam pelaporan Corporate Social Responsibility: Analisis Semiotik Atas Sustainability Reporting PT. Kaltim Prima Coal dan PT. Perkebunan Nusantara XIII (Persero)â€. E-journal Ekonomi Bisnis dan Akuntansi, Volume 1, pp. 32-41.Ernst and Young. (2014). Integrated Reporting â€“ Elevating Value.Â  http://www.ey.com. (diakses pada 25 Oktober 2015)Â  Feldman, Martha S., and Kaj SkoÂ¨ldberg. 2002. Stories and the rhetoric of contrariety: Subtexts of organizing (change). Culture and Organization 8 (4): 275â€“92.Ferdinand de. Saussure,Â  (1996). Pengantar Linguistik Umum. Yogyakarta: Gadjah Mada University Press.Financial Accounting Standards Board (FASB). 1978. â€œStatement of Financial Accounting Concepts No.1: Objectives of Financial Reporting by Business Enterprisesâ€. Stamford. Connecticut.Fitriany, Kiki. (2009) â€œRetorika Dalam Pelaporan keuangan: Analisis Narrative Text Dalam Annual Report perusahaan yang mengalami Kerugianâ€, Skripsi, Semarang : Fakultas Ekonomi Universitas Diponegoro.Fontaine, Charles. Antonie Haarman dan Stefan Schmid.(2006, Desember). â€œThe Stakeholder Theoryâ€. Research paper, Edlays Education 1.1Gentur Agustinus Naru (2008), mahasiswa Universitas Padjajaran Program Studi Ilmu Komunikasi Jurnalistik yang berjudul â€Analisis Semiotika Roland Barthes Terhadap Representasi Citra Presiden Berasal dari dimaknai menghasikan Bahasa Kata-kata Ide.Harahap, Sofyan Syafiri. (2008). Analisa Kritis atas Laporan Keuangan. Jakarta; PT. Raja Grafindo Persada.Haslinda Yusoff, Glen Lehman, (2009) "Corporate environmental reporting through the lens of semiotics", Asian Review of Accounting, Vol. 17 Issue: 3, pp.226-246, https://doi.org/10.1108/13217340910991938Â Holsti, O.R., (1969). Content Analysis for the Social Sciences and Humanities, Philipines: Addison-Wesley Publishing Company, Inc.http://www.jagoakuntansi.com/2015/12/integrated-reporting-sebuah-pendekatan -baru-dalam-pelaporan-nilai-perusahaan/, retrived on 20 Oktober 2016IIRC, (2013) (International Integrated Reporting Council), The International Integrated Reporting Framework.Â Jalaludin Rakhmat, (2011). â€œRetorika Modern dan Pendekatan Praktisâ€ cet. 15 Bandung : PT. Remaja Rosdakarya. 2011.Â Jupe, Robert. (2005, Juli). â€œDisclosures in Corporate Enivronmental Reports: A Test of Legitimacy Theoryâ€. Working Paper, No. 91Â Kartika, (2009). Faktor-Faktor Yang Mempengaruhi Audit Delay di Indonesia (Studi Empiris Pada Perusahaan-Perusahaa LQ 45 Yang Terdaftar di Bursa Efek Jakarta), Jurnal Bisnis dan Ekonomi (JBE), Fakultas Ekonomi Universitas Stikubank Semaran.Keraf, Kahar, (1994). Argumentasi dan Narasi. Jakarta: Gramedia.Khomsiyah, (2005), â€œlaporan keuangan adalah hasil dari proses akuntansi yang dapat digunakan sebagai alat komunikasiâ€. E-journal Ekonomi Bisnis dan Akuntansi, Volume 1, pp 40-45Kohut, G.F., dan A.H. Segars. 1992. â€œThe Presidentâ€Ÿs Letter to Stakeholders : AnExamination of Corporate Communication Strategyâ€. Journal ofBusiness Communication, Vol. 29, No.1, Hal. 7-21Â Lim, Sha May dan Trevor Wilmshurt. (2010). â€œBlowing in the Wind Legitimacy Theory. An Environmental Incident and Dissclosureâ€. Research Paper, Australia: Unibersity of TasmaniaÂ Littlejohn, Stephen W. (2009). Theories of Human Communication Edisi 9, Jakarta: Salemba Humanika.Â Martani, Dwi. Pelaporan Berkelanjutan dan Pelaporan Terintegrasi. http://staff.blog.ui.ac.id/martani/. (diakses pada 2 November 2015).Martin Muderspach Thellefsen, Torkild Thellefsen, Bent SÃ¸rensen, (2017). "Information as signs: A semiotic analysis of the information concept, determining its ontological and epistemological foundations", Journal of Documentation, https://doi.org/10.1108/JD-05-2017-0078Â Martono, (2016). â€œEvolusi dalam Pelaporan Keuangan Perusahaan : Analisis Semiotik atas Integrated Reporting PT Pertaminaâ€. Skripsi, Pontianak: Fakultas Ekonomi dan Bisnis Universitas Tanjungpura.(Mercier, 1999). all of the agents for whom the firmâ€™s development and good health are of prime concern) Vol. 5 No.1. hal 220-300Moleong, Lexy J. (2002). Metodologi Penelitian Kualitatif Edisi Revisi. Bandung: PT Remaja RosdakaryaÂ Munawir. (2004). Analisis Laporan Keuangan, Edisi ke-4. Yogyakarta: Liberty. Yogyakarta. Ikatan Akuntansi Indonesia (IAI). 2004. Pernyataan Standar Akuntansi Keuangan (PSAK ). Jakarta: Salemba Empat.Â Munawir., (2001), Analisa Laporan Keuangan, Yogyakarta: Liberty.Â Norman K. Denkin, (2009),Â Metodologi Penelitian Kualitatif, Bandung: Remaja Rosdakarya, hal. 330Nugroho, Firman Aji, (2009). â€œRetorika dalam Pelaporan Corporate Social Responsibility: Analisis Semiotik atas Sustainability Report PT Aneka Tambang Tbkâ€. Skripsi, Semarang: Fakultas Ekonomi Universitas Dipenogoro.Oktaviani, (2017) : â€œRetorika Dalam Pelaporan Keuangan Perusahaan : Analisis Semiotik atas Annual Report PT Timah TbkPerelman, Ch. (1982). â€œThe Realm of Rhetoric. Klubackâ€. Notre Dame: The University of Notre Dame Press.Piliang, Yasraf. (2005). Hipersemiotika: Tafsir Cultural Study Atas Matinya Makna. Yogyakarta: Jalasutra.Priyanti, (2012). â€œMengeksplore kepedulian dan lingkungan sosial Â  PT. AKR Corporindo Tbk, melalui laporan CSR ( Studi semiotika dan indeks pengungkapan.Pradana, Fadillah Ariza, (2016). â€œKajian Semiotik Laporan Tahunan PT.Bank Rakyat Indonesia, Tbk. Sebelum dan Setelah menjadi Pemenang dalam Annual Report Awardâ€. Skiripsi, Malang: Fakultas Ekonomi Universitas Negri Malang.PricewaterhouseCoopers. 2013. Point of View Integrated Reporting â€“ Going beyond the financial results. http://www.pwc.com.Satori, Djamâ€™an dan Aan Komariah. (2009). Metedologi Penelitian Kualitatif. Bandung: AlfabetaSuchman, Mark C. (1995). Managing Legitimacy: Strategic and Institutional Approaches. The Academy of Management Review Vol. 20 No. 3. pp. 571-610. http://www.jstor.org/stable/258788.Sugiyono. (2012). Memahami Penelitian Kualitatif. Bandung: AlfabetaSuwardjono, (2005). Teori Akuntansi : pelaporan Keungan Edisi Ketiga. Yogyakarta : BPFE.SAB&T. Integrated Reporting â€“ A guide. http://www.nexiasabt.co.za/. (diakses pada 25 Oktober 2015).The International Integrated Reporting Council (IIRC). 2013. The International <IR> Framework. http://www.theiirc.org. (diakses pada 2 November 2015).Utomo, Sukarno Tri, (2010). â€œ Rasisme dalam Pelaporan Akuntansi: Analisis atas Annual Report PT. Perusahaan Gas Negara, Tbk dan PT. Aneka Tambang, Tbk dalam Prespektif Teori Komunikasi Aksi Habernasâ€. Skripsi, Semarang: Fakultas Universitas Diponegoro.Widiyastuti, Yuni. (2012). â€œEvolusi dalam Pelaporan Keuangan Perusahaan : Analisis Semiotik atas Integrated Reportingâ€. Skripsi, Semarang: Universitas Diponogoro.Wahyuni, Ersa Tri. 2015. Tuntutan Pelaporan Keuangan Semakin Kompleks : Tantangan Masa Depan Akuntan. http://etw-accountant.com/. (diakses pada 5 November 2015).Young, Joni J. (2003). â€œ Consstructing, Persuading and Silencing: The Rhetoric of Accounting Standartâ€. Skripsi, Albuquerque : University of New Mexico.Yusita kusumarini, (2006), teori semiotic: universitas Kristen petra.Zuhroh, dan Sukmawati. (2003). Analisis pengaruh luas pengungkapan sosial dalam laporan tahunan perusahaan terhadap reaksi investor (studi kasus pada perusahaan-perusahaan high profile di BEJ). Simposium Nasional Akuntansi VI, 1314-1341.